Sociolinguistic Analysis of the Local Wisdom Values in the Marriage Customs of the Lawelu Village Community Ulu Moro'o Sub District - Gulo, Ceria Putri Damai; Waruwu, Yaredi; Harefa, Afore Tahir; Telumbanua, Yasminar Amaerita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research explores the local wisdom values embedded in the marriage customs of the Lawelu village community through a sociolinguistic perspective. Marriage customs in Lawelu village, characterized by traditional ceremonies such as famaigi niha, fame’e laeduru, fanunu manu, femanga bawi nisila hulu, mangötö wongi, famözi aramba, folau bawi, falöwa, mame’e gö/famasao, dan mamuli nukha/manga gahe, are rich in symbolic language and cultural expressions that reflect community values and social norms. Using qualitative methods, including interviews and participant observations, the study examines how these customs communicate respect, solidarity, and familial bonds, reinforcing community identity and cultural continuity. The findings reveal that the linguistic elements used during marriage rituals serve not only as a means of communication but also as a vehicle for transmitting moral values and maintaining social cohesion. This research contributes to understanding how socioliunguistic practices in traditional ceremonies preserve local wisdom and promote cultual sustainability in rural communities, especially in Lawelu village, ulu moro’ö.